PENGARUH GAYA MENGAJAR GURU DAN KEBIASAAN BELAJAR TERHADAP HASIL BELAJAR (Studi Pada Mata Pelajaran IPS Peserta Didik Di SMP Negeri Satu Atap Plakpak Kecamatan Pegantenan Kabupaten Pamekasan) - Achmad Djauhari (Jurnal Penelitian dan Pendidikan IPS, 2016)
The objective of this research was to found scientific information whether there was significant effect of Teacher’s Teaching Styles toward students’ learning outcomes whether there was significant effect of students’ learning habits toward students’ learning outcomes and whether there was significant effect of Teacher’s Teaching Styles and students’ learning habits simultaniousely toward students’ learning outcomes of social science subject at Stat Unior High School Satu Atap Plakpak of Pegantenan District in Pamekasan Regency Metode used of this research are questionnaire and documentation of Teacher’s Teaching Styles that was arranged to get data about social economy status, this questionnaire was consisted of sixteen questions students’ learning habits questionnaire was arranged to get students’ learning habits, this questionnaire consisted of seventeen questions. While documentation was taken from report score of  State Junior High School Satu Atap Plakpak Pegantenan District Pamekasan Regency in 2016-2017 academic year. On the basis of evidence and analysis result of Teacher’s Teaching Styles data with correlation coefficient 0,133 signification level 5% and probability 0.000. because probability smaller than 0,05 thus students’ habitual learning hypothesis had significant effect toward students’ learning outcomes while correlation index 0,113 and signification level 0,5% with probability 0,000. Because probability smaller than 0,05 thus students’ learning habits hypothesis had significant effect toward students’ learning outcomes, while the result of multy regression showed that R-acount 0,39 and R table 0,125. Because R-acount bigger than R-table thus Teacher’s Teaching Styles and students’ learning habits had significant effect toward students’ learning outcomes and if it tested using F-account 5,929 and signification level 5% with probability 0,007 if F-table compared with documentation 37-1 = 36 found a number 0,133. because probability bigger than 0,05 and F-acount bigger than F-table thus Teacher’s Teaching Styles and students’ learning habits hypothesis had significant effect collectively toward students’ learning outcomes of social science subject at Satu Atap Plakpak of Pegantenan Distrik in Pamekasan Regency.